High-sensitivity detection of Concanavalin A using MoS2-based field effect transistor biosensor. (30th March 2021) - Ma, Mingyang; Chao, Lemeng; Zhao, Yuhang; Ding, Jiafeng; Huang, Zhongchao; Long, Mengqiu; Wang, Fuliang; Jiang, Jie; Liu, Zhengchun
Abstract: The specific interaction between sugar and lectin plays a key role in various human diseases and projects remarkable significance to the development of a lectin biosensor for diagnosis and drug discovery. An inorganic nano MoS2 field-effect transistor (FET)-based D-Mannose biosensor was developed in this paper using a simple assembly process. First, gold nanoparticles were functionalized on the surface of MoS2 . Then, the β -mercaptoethylamine was self-assembled on the gold surface via Au–S bonds to derivatize amino groups. Finally, the probe molecules D-Mannose for biological protein were immobilized on the FET via the Schiff base reaction. Results from scanning electron microscope and x-ray photoelectron spectroscopy analysis confirmed the entire assembly procedure and the feasible interaction of the FET sensor with Concanavalin A (ConA). The fabricated FET biosensors can reliably detect the target ConA with a detection limit below 105 nm. The current study shows the potential of MoS2 FET biosensors for ConA specific detection and clarifies the design of biosensors for the early diagnosis of glycomics and drug screening in medicine.